Design Of A 2.4 Mw Low-Head Hydroelectric Power Plant (PLTA) Using a Kaplan/Bulb Turbine for Rural Electrification in Bolaang Mongondow Regency - Dony Lumenta; Marson James Budiman; Donald Bastian Noya (Journal of Social Research, 2026)
This study addresses the critical role of effective organizational and infrastructural management in improving operational efficiency and service delivery. Despite numerous initiatives, many institutions continue to experience challenges in workflow optimization, resource allocation, and stakeholder engagement, which hinder overall performance. The research aims to analyze the impact of system integration and process management on operational outcomes, focusing on measurable indicators of productivity, efficiency, and service quality. A mixed-methods approach was employed, combining quantitative data collection from institutional records and performance metrics with qualitative insights obtained through structured interviews and observational analysis. Data were analyzed using statistical and thematic methods to identify patterns, correlations, and underlying factors influencing outcomes. The results indicate that coordinated workflow systems, supported by adequate infrastructure and clear operational protocols, significantly enhance efficiency and service delivery. Key bottlenecks were identified, and strategic interventions were proposed, demonstrating tangible improvements in performance metrics. In conclusion, the study confirms that integrating process management with infrastructural support is essential for optimal institutional performance. Future research is recommended to explore longitudinal effects of these interventions across different organizational contexts, as well as to investigate the role of emerging technologies in further enhancing operational effectiveness and service quality.